Decolonizing policing: Indigenous patrols, counter-policing and safety. (November 2016) - Porter, Amanda
This article examines the everyday operation and politics of Indigenous patrols, community-run initiatives with formal agendas that focus on keeping young people safe and preventing contact between young people and the state police. Specifically, it presents fieldwork findings and interview data conducted over three years on various patrols across New South Wales, Australia. In this article, patrols are used as a lens through which to critically examine contemporary issues in the policing of Indigenous Australian communities and as a way of exploring what it means to decolonize the institutions and activities of policing. The research findings demonstrate the complexity of processes of decolonization and raise broader questions concerning how knowledge is produced about Indigenous communities, both by governments and within academia.